2020
DOI: 10.1111/obr.13082
|View full text |Cite
|
Sign up to set email alerts
|

Male adiposity, sperm parameters and reproductive hormones: An updated systematic review and collaborative meta‐analysis

Abstract: Summary The present updated systematic review and meta‐analysis aims to summarize the evidence from published studies with low risk for any important bias (based on methodological quality assessment) investigating the potential associations of adiposity with sperm quality and reproductive hormones. We conducted a systematic search of the literature published in MEDLINE‐PubMed and EMBASE through June 2019. Based on the criteria in our review, 169 eligible publications were used for data abstraction. Finally, 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 111 publications
1
55
0
Order By: Relevance
“…Growing evidence is also focusing on genetic factors and it is indeed well established that genetic causes account for 10%-15% of infertility cases, including chromosomal abnormalities and single-gene mutations (37). In addition to these well-known factors, growing evidence suggests that obesity, unhealthy diet, cigarette smoking and pollution may seriously affect sperm parameters and reduce male fertility (38)(39)(40)(41). Again, besides bacterial semen infections, the presence of HPV on the male partner is now considered a risk factor both for natural and assisted reproduction outcome (42,43).…”
Section: Male Risk Factorsmentioning
confidence: 99%
“…Growing evidence is also focusing on genetic factors and it is indeed well established that genetic causes account for 10%-15% of infertility cases, including chromosomal abnormalities and single-gene mutations (37). In addition to these well-known factors, growing evidence suggests that obesity, unhealthy diet, cigarette smoking and pollution may seriously affect sperm parameters and reduce male fertility (38)(39)(40)(41). Again, besides bacterial semen infections, the presence of HPV on the male partner is now considered a risk factor both for natural and assisted reproduction outcome (42,43).…”
Section: Male Risk Factorsmentioning
confidence: 99%
“…Unfortunately, there were no RCTs looking at the effects of weight loss on fertility outcomes in men. The previous review included two non‐randomized studies which suggested weight loss could help improve sperm concentration, motility and morphology 68,69 and recent systematic review evidence, from cohort and cross‐sectional studies, suggests maintaining a healthy weight is important for sperm quality 70 . All trials included in our review explored the effect of weight loss of the woman seeking pregnancy alone; the weight of their partner was not considered.…”
Section: Discussionmentioning
confidence: 99%
“…Hormones have a decisive influence on the formation and functioning of the reproductive system of animals, both in females and males [6][7][8]. Hormone receptor gene polymorphisms may be good markers of aspects of spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%